Use of remote sensing to estimate paddy area and production a handbook. - Rotairo, Lea
A substantial portion of the world rice is produced and consumed in Asia and the Pacific. As much of the region population depends on rice farming, timely and good quality agricultural estimates and forecasts are essential for effective policy formulation. Recent advances in remote sensing offer a viable alternative to traditional methods of compiling agricultural statistics.